ANALYSIS OF LINGUISTIC AND TRANSLATION ASPECTS IN AVIATION TERMINAL SYSTEMS (Proceedings of International Educators Conference, 2024)
The article examines linguistic and translation aspects within the English aviation terminology system. It explores methods for enriching English aviation terminology, conducts lexical-semantic and structural analyses, and discusses strategies for translating multi-component terms, abbreviations, and acronyms from aviation English into Russian.